Implementing Motor Unit Number Index (MUNIX) in a large clinical trial: Real world experience from 27 centres. Issue 8 (August 2018) - Neuwirth, Christoph; Braun, Nathalie; Claeys, Kristl G.; Bucelli, Robert; Fournier, Christina; Bromberg, Mark; Petri, Susanne; Goedee, Stephan; Lenglet, Timothée; Leppanen, Ron; Canosa, Antonio; Goodman, Ira; et al.
Highlights: MUNIX was implemented in 27 centres for a large ALS study. For the qualification, around 40% of measurements had to be repeated. Prior face-to-face training and continuous support during the process proved to be helpful. Abstract: Objective: Motor Unit Number Index (MUNIX) is a quantitative neurophysiological method that reflects loss of motor neurons in Amyotrophic Lateral Sclerosis (ALS) in longitudinal studies. It has been utilized in one natural history ALS study and one drug trial (Biogen USA) after training and qualification of raters. Methods: Prior to testing patients, evaluators had to submit test-retest data of 4 healthy volunteers. Twenty-seven centres with 36 raters measured MUNIX in 4 sets of 6 different muscles twice. Coefficient of variation of all measurements had to be <20% to pass the qualification process. MUNIX COV of the first attempt, number of repeated measurements and muscle specific COV were evaluated. Results: COV varied considerably between raters. Mean COV of all raters at the first measurements was 12.9% ± 13.5 (median 8.7%). Need of repetitions ranged from 0 to 43 (mean 10.7 ± 9.1, median 8). Biceps and first dorsal interosseus muscles showed highest repetition rates. MUNIX variability correlated considerably with variability of compound muscle action potential. Conclusion: MUNIX revealed generally good reliability, but was rater dependent and ongoing support for raters was needed. Significance: MUNIX can be implemented in large clinical trials as an outcome measure after training and a qualification process.